A method for purifying hydrogen peroxide
Through the preparation of the modified hollow fiber composite film, the problem of oxidation and degradation of membrane materials in high-concentration hydrogen peroxide treatment is solved, and the continuous and effective purification of hydrogen peroxide and the long-term stability of membrane materials are achieved.
Patent Information
- Application Number
- CN202411805076.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-10
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrogen peroxide purification, in particular to a method for purifying hydrogen peroxide. Background Art
[0002] Hydrogen peroxide (aqueous hydrogen peroxide solution) is a green and environmentally friendly oxidant that plays an important role in the chemical industry. Since hydrogen peroxide was developed in 1811, the existing technology has made more and more in-depth research on hydrogen peroxide, and the application fields of hydrogen peroxide have become more and more diversified. At present, hydrogen peroxide is mainly used in biomedicine as pharmaceutical additives, low-temperature plasma sterilization, biosensors, pesticide additives, etc.; in the chemical industry, it is mainly used as an oxidant and industrial raw materials; in the food industry, it is mainly used as a food additive; in aerospace, hydrogen peroxide can be combined with borohydride and other cyanogens to form fuel cells and used as a propulsion aid; in the electronics industry, it is mainly used for electrode modification, disassembly of discarded circuit boards, etc.
[0003] In the prior art, the industrial production methods of hydrogen peroxide mainly include electrolysis, direct hydrogen and oxygen synthesis, isopropanol oxidation, oxygen cathode reduction, anthraquinone method, etc. At present, the anthraquinone method for preparing hydrogen peroxide has the advantages of large-scale, low energy consumption, low cost and easy operation in the production process, and has gradually become the mainstream hydrogen peroxide production process. It uses an organic solvent of alkyl anthraquinone as a raw material, and after hydrogen is introduced under certain pressure and temperature conditions for hydrogenation, it is contacted with air or oxygen for countercurrent oxidation, and then subjected to post-treatment such as extraction, regeneration, refining, and concentration to finally obtain an industrial-grade hydrogen peroxide with a mass fraction of 20-30%. However, the industrial-grade hydrogen peroxide prepared by the anthraquinone method contains a certain amount of organic impurities, metal impurities, etc., and its organic impurities mainly include: heavy aromatics, trioctyl phosphate, 2-methylcyclohexyl acetate, anthraquinone and its derivatives, etc. The impurities in industrial-grade hydrogen peroxide seriously affect its downstream application effect, so the purification of industrial-grade hydrogen peroxide has important technical significance and value.
[0004] The existing methods for purifying industrial-grade hydrogen peroxide mainly include: distillation, resin adsorption, membrane separation, extraction, etc. Among them, the distillation method and the extraction method have the defects of high processing cost, high energy consumption, and cumbersome post-processing. The resin adsorption method and the membrane separation method have become the mainstream methods for purifying industrial-grade hydrogen peroxide. In the process of treating industrial-grade hydrogen peroxide by membrane separation, the industrial-grade hydrogen peroxide with a mass fraction of 20-30% is directly treated. Due to the low concentration of industrial-grade hydrogen peroxide, there are problems of low processing efficiency, high processing energy consumption and unstable processing effect. Therefore, in the prior art, the industrial-grade hydrogen peroxide is generally concentrated first, and after it is concentrated to a concentration of more than 45wt%, a subsequent membrane separation treatment is performed; for example, Chinese patent CN115557470A discloses a production method and a production device for electronic-grade hydrogen peroxide, which uses an evaporator and a distillation tower to concentrate the industrial-grade hydrogen peroxide to a concentration of more than 50%, and then a subsequent two-stage reverse osmosis mechanism membrane separation is performed.
[0005] Although this patent can overcome the aforementioned defects of directly treating low-concentration industrial-grade hydrogen peroxide, in the actual operation process of industrial-scale production, under the membrane separation conditions of continuous, large flow, and high operating pressure, due to the high concentration of concentrated hydrogen peroxide and its strong oxidizing properties, it is easy to cause oxidative degradation of membrane materials, which in turn leads to reduced separation performance and mechanical properties of membrane materials, which not only affects the membrane separation treatment effect of hydrogen peroxide, but also leads to a short effective service life of membrane materials, requiring frequent maintenance and replacement, and high treatment costs. At the same time, the presence of a large amount of metal impurities in concentrated hydrogen peroxide not only affects the treatment effect of membrane materials on organic impurities, but also reduces the oxidation resistance of membrane materials, accelerates the oxidative degradation of membrane materials, and further leads to the deterioration of separation performance, mechanical properties, and service life of membrane materials.
[0006] Furthermore, in the existing membrane separation process for high-concentration hydrogen peroxide, water molecules are easily attached and aggregated on the surface of the membrane material, affecting the continuous membrane separation treatment effect and treatment efficiency of high-concentration hydrogen peroxide, resulting in poor treatment stability of the membrane separation treatment of high-concentration hydrogen peroxide under continuous, large flow, and high operating pressure membrane separation conditions, and it is impossible to achieve the ideal membrane separation continuous treatment effect and treatment efficiency. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for purifying hydrogen peroxide, which can effectively avoid the adverse effects of the strong oxidizing property of high-concentration hydrogen peroxide on membrane materials under the conditions of continuous, large flow and high operating pressure membrane separation, and further avoid the adverse effects of metal impurities in concentrated hydrogen peroxide on membrane materials while maintaining good service life and mechanical properties of the membrane materials, and can synchronously separate organic impurities and metal impurities in concentrated hydrogen peroxide to achieve continuous and effective purification of hydrogen peroxide; and in continuous membrane separation treatment, effectively avoid the attachment and aggregation of water molecules on the surface of the membrane material, and improve the stability of continuous treatment.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for purifying hydrogen peroxide comprises the following steps: preparing a modified hollow fiber composite membrane, concentrating, primary membrane separation, and secondary membrane separation.
[0010] The method for preparing the modified hollow fiber composite membrane comprises the following steps: preparing pre-modified activated carbon, primary treatment, and secondary treatment.
[0011] The method for preparing pre-modified activated carbon comprises the following steps: adding nano activated carbon into a reaction kettle containing toluene, stirring for 20-30 minutes, continuously adding acrylic ester monomers, crosslinking monomers and silane modifiers, and then completely replacing the air in the reaction kettle with nitrogen; stirring and heating to 50-55° C. under the protection of nitrogen atmosphere, keeping the temperature and stirring for 30-40 minutes, stirring and heating to 80-85° C. and keeping the temperature; stirring and adding initiator, continuing to keep the temperature and stirring for 2.5-3.5 hours, cooling to room temperature, filtering and separating to obtain solids; washing the solids 2-3 times with 4-5 times the weight of toluene, and drying to obtain pre-modified activated carbon.
[0012] In the preparation of the pre-modified activated carbon, the average particle size of the nano-activated carbon is 90-100 nm;
[0013] The acrylic acid ester monomers are n-butyl methacrylate and methyl acrylate; the weight ratio of n-butyl methacrylate to methyl acrylate is 3-3.2:1;
[0014] The cross-linking monomer is N,N-dimethyl methacrylamide;
[0015] The silane modifier is methacryloxymethyltriethoxysilane;
[0016] The initiator is azobisisobutyronitrile.
[0017] In the preparation of the pre-modified activated carbon, the weight ratio of the nano-activated carbon, toluene, acrylic ester monomer, cross-linking monomer, silane modifier and initiator is 15-16:80-85:63-66:7-8:3-3.3:2-2.5.
[0018] The method for the one-time treatment is as follows: adding the pre-modified activated carbon into anhydrous ethanol, stirring for 10-20 minutes, and then continuously adding polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate, stirring for 20-30 minutes to obtain a one-time treatment liquid; then completely immersing the dried silicone rubber / polysulfone hollow fiber composite membrane into the one-time treatment liquid, and controlling the immersion pressure to be 0.12-0.15MPa, and after immersing for 30-50 seconds, taking out the immersed silicone rubber / polysulfone hollow fiber composite membrane, transferring it into a constant temperature box, drying it at 85-90°C for 4-5 hours, heating it to 135-140°C, and heat-treating it at the temperature for 20-30 minutes to obtain a one-time treatment composite membrane.
[0019] In the one-time treatment, the pore size of the silicone rubber / polysulfone hollow fiber composite membrane is 0.2-0.3 μm, the inner diameter of the membrane is 0.7-0.8 mm, and the membrane wall thickness is 0.5-0.6 mm;
[0020] The weight ratio of pre-modified activated carbon, anhydrous ethanol, polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate is 7-7.2:100-105:12-13:1.4-1.5:0.08-0.1;
[0021] The volume ratio of the dry silicone rubber / polysulfone hollow fiber composite membrane to the primary treatment liquid is 1:3-3.5.
[0022] The secondary treatment method is as follows: adding the pre-modified activated carbon into deionized water, stirring for 10-20 minutes, then adding zinc nitrate hexahydrate and 2-methylimidazole, and continuing stirring for 20-30 minutes to obtain a secondary treatment liquid; then completely immersing the primary treatment composite membrane in the secondary treatment liquid, immersing for 30-40 minutes, taking out the immersed primary treatment composite membrane, transferring it into a constant temperature box, standing at 50-55°C for 2-3 hours, and drying at 90-95°C for 4-5 hours to obtain a modified hollow fiber composite membrane.
[0023] In the secondary treatment, the weight ratio of pre-modified activated carbon, deionized water, zinc nitrate hexahydrate, and 2-methylimidazole is 4-4.5:300-305:0.6-0.62:8.3-8.4;
[0024] The volume ratio of the primary treatment composite membrane to the secondary treatment liquid is 1:2.5-3.
[0025] The concentration method is to introduce industrial-grade hydrogen peroxide with a mass concentration of 20-30% into a falling film evaporator, concentrate it to a mass concentration of 50-55% through falling film evaporation, obtain concentrated hydrogen peroxide and introduce it into a temporary storage tank to cool it to room temperature for standby use.
[0026] The primary membrane separation method comprises the following steps: assembling the modified hollow fiber composite membrane into the hollow fiber membrane assembly, and then respectively loading the assembly into the primary membrane separation device and the secondary membrane separation device; continuously introducing the concentrated hydrogen peroxide in the temporary storage tank into the primary membrane separation device; and controlling the inlet flow rate of the concentrated hydrogen peroxide to be 380-400 kg / h and the membrane separation pressure to be 0.23-0.25 MPa; and after continuously performing the primary membrane separation, obtaining the primary membrane separation liquid, and continuously introducing the liquid into the secondary membrane separation device.
[0027] In the primary membrane separation, the effective membrane area of the primary membrane separation device is 18-20m 2 .
[0028] The secondary membrane separation method is that the secondary membrane separation device continuously receives the primary membrane separation liquid from the primary membrane separation device, controls the membrane separation pressure to be 0.27-0.3MPa, and after continuously performing the secondary membrane separation, obtains the purified hydrogen peroxide product, and continuously introduces it into the product tank for storage.
[0029] In the two-stage membrane separation, the effective membrane area of the two-stage membrane separation device is 23-25m 2 .
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The method for purifying hydrogen peroxide of the present invention comprises the following steps: in the preparation of the modified hollow fiber composite membrane, in the step of preparing the pre-modified activated carbon, the nano-activated carbon is treated with an acrylate monomer, a cross-linking monomer and a silane modifier, so that cross-linkable groups (acrylate groups, silane groups, etc.) can be introduced on the surface of the nano-activated carbon, effectively improving the composite performance of the subsequent pre-modified activated carbon and silicone rubber, and at the same time improving the hydrophobicity of the nano-activated carbon; then in a first treatment step, the pre-modified activated carbon is cross-linked with polymethyloctylsiloxane and silane coupling agent KH-550 through the cross-linkable groups on its surface. Through cross-linking with silicone rubber monomers, it can be effectively compounded to the outer surface of silicone rubber / polysulfone hollow fiber composite membrane to form a cross-linked porous composite structure, and the hydrophobicity of the primary treatment composite membrane can be further improved by silane coupling agent KH-550, so as to avoid the attachment and aggregation of water molecules on the surface of the membrane material and improve the stability of continuous membrane separation treatment; through the compounding of pre-modified activated carbon, polymethyl octyl siloxane and silicone rubber / polysulfone hollow fiber composite membrane, it can improve its mechanical properties while improving the stability and oxidation resistance of the membrane material, and improve its resistance to adverse factors during application. Then, in the secondary treatment step, the pre-modified activated carbon is combined with the in-situ generated metal organic framework material to further improve the stability, oxidation resistance and mechanical properties of the membrane material through chemical bonding and interface bonding, extend the effective service life of the membrane material, improve the adaptability and separation stability of the membrane material to continuous, large flow and high operating pressure, and at the same time improve the targeted separation performance of the membrane material for impurities (especially metal impurities) in hydrogen peroxide; then, the industrial-grade hydrogen peroxide is concentrated, separated by a primary membrane and separated by a secondary membrane to obtain a purified hydrogen peroxide product; the aforementioned technical means cooperate and work synergistically with each other, and can effectively avoid the adverse effects of the strong oxidizing property of high-concentration hydrogen peroxide on the membrane material under the membrane separation conditions of continuous, large flow and high operating pressure, while maintaining the good service life and mechanical properties of the membrane material, further avoid the adverse effects of metal impurities in concentrated hydrogen peroxide on the membrane material, can synchronously separate organic impurities and metal impurities in concentrated hydrogen peroxide, and realize continuous and effective purification of hydrogen peroxide; and in the continuous membrane separation treatment, effectively avoid the attachment and aggregation of water molecules on the surface of the membrane material, and improve the stability of continuous treatment.
[0032] (2) The method for purifying hydrogen peroxide of the present invention is used to purify industrial-grade hydrogen peroxide having a mass concentration of 28%, an organic carbon content TOC of 557 ppm, a chloride content of 303 ppb, a nitrate content of 50 ppb, a sulfate content of 78 ppb, a phosphate content of 42 ppb, a silicon content of 51 ppb, a calcium content of 10 ppt, a potassium content of 77 ppt, a sodium content of 168 ppt, and an iron content of 16 ppt; the organic carbon in the purified hydrogen peroxide product is The TOC content is 3.64-3.67ppm, the chloride content is 5.39-5.42ppb, the nitrate content is 8.12-8.14ppb, the sulfate content is 4.80-4.85ppb, the phosphate content is 2.95-2.97ppb, the silicon content is 1.66-1.69ppb, the calcium content is 2ppt, the potassium content is 4-5ppt, the sodium content is 5-6ppt, the iron content is 2ppt, and the evaporation residue content is 6.7-6.8μg / g.
[0033] (3) In the method for purifying hydrogen peroxide of the present invention, the water contact angle of the modified hollow fiber composite membrane used is 108-109°; and after the modified hollow fiber composite membrane in the primary membrane separation device has been in continuous operation for 90 days, its water contact angle is 105-107°.
[0034] (4) The method for purifying hydrogen peroxide of the present invention is used to purify industrial-grade hydrogen peroxide having a mass concentration of 28%, an organic carbon content TOC of 557 ppm, a chloride content of 303 ppb, a nitrate content of 50 ppb, a sulfate content of 78 ppb, a phosphate content of 42 ppb, a silicon content of 51 ppb, a calcium content of 10 ppt, a potassium content of 77 ppt, a sodium content of 168 ppt, and an iron content of 16 ppt; the purified hydrogen peroxide product obtained on the 90th day after continuous primary membrane separation and secondary membrane separation has an organic carbon content TOC of 3.83-3.86 ppm, a chloride content of 5.70-5.75 ppb, nitrate content is 8.51-8.54ppb, sulfate content is 5.06-5.10ppb, phosphate content is 3.11-3.14ppb, silicon content is 1.76-1.79ppb, calcium content is 3ppt, potassium content is 4-6ppt, sodium content is 5-7ppt, iron content is 3ppt, and evaporation residue content is 7.1-7.2μg / g; and after 90 days of continuous operation, the backwashing interval required for the modified hollow fiber composite membrane in the primary membrane separation device and the secondary membrane separation device is no significantly different from that before continuous operation, which can maintain good membrane separation treatment efficiency for a long time and the effective service life of the membrane material is long. DETAILED DESCRIPTION
[0035] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0036] Example 1
[0037] The present embodiment provides a method for purifying hydrogen peroxide, which purifies industrial-grade hydrogen peroxide prepared by an anthraquinone method; the mass concentration of the industrial-grade hydrogen peroxide is 28%, the organic carbon content TOC is 557 ppm, the chloride content is 303 ppb, the nitrate content is 50 ppb, the sulfate content is 78 ppb, the phosphate content is 42 ppb, the silicon content is 51 ppb, the calcium content is 10 ppt, the potassium content is 77 ppt, the sodium content is 168 ppt, and the iron content is 16 ppt.
[0038] Specifically, the method for purifying the hydrogen peroxide is as follows:
[0039] 1. Preparation of modified hollow fiber composite membrane
[0040] 1) Preparation of pre-modified activated carbon
[0041] The nano-activated carbon was put into a reactor filled with toluene, and after stirring for 20 minutes, acrylic ester monomers, cross-linking monomers and silane modifiers were continuously added, and then the air in the reactor was completely replaced by nitrogen. Under the protection of nitrogen atmosphere, the temperature was raised to 50°C with stirring, and after stirring and keeping warm for 30 minutes, the temperature was raised to 80°C with stirring and keeping warm; the initiator was stirred and added, and the stirring and keeping warm for 2.5 hours was continued. After cooling to room temperature, the solid matter was separated by filtration to obtain the solid matter; the solid matter was washed 3 times with 4 times the weight of toluene, and then dried to obtain the pre-modified activated carbon.
[0042] Among them, the average particle size of nano activated carbon is 90nm.
[0043] The acrylic acid ester monomers are n-butyl methacrylate and methyl acrylate; the weight ratio of n-butyl methacrylate to methyl acrylate is 3:1.
[0044] The cross-linking monomer is N,N-dimethyl methacrylamide.
[0045] The silane modifier is methacryloxymethyltriethoxysilane.
[0046] The initiator is azobisisobutyronitrile.
[0047] The weight ratio of nano activated carbon, toluene, acrylate monomer, cross-linking monomer, silane modifier and initiator is 15:80:63:7:3:2.
[0048] 2) One-time processing
[0049] The pre-modified activated carbon was put into anhydrous ethanol, stirred for 10 minutes, and then polymethyloctylsiloxane, silane coupling agent KH-550 and dibutyltin dilaurate were added, and stirred for 20 minutes to obtain a primary treatment liquid; then the dried silicone rubber / polysulfone hollow fiber composite membrane was completely immersed in the primary treatment liquid, and the immersion pressure was controlled to be 0.12MPa. After immersion for 30 seconds, the impregnated silicone rubber / polysulfone hollow fiber composite membrane was taken out and transferred to a constant temperature box. After drying at 85°C for 4 hours, the temperature was raised to 135°C and heat-treated for 20 minutes to obtain a primary treatment composite membrane.
[0050] The pore size of the silicone rubber / polysulfone hollow fiber composite membrane is 0.25 μm, the inner diameter of the membrane is 0.8 mm, and the membrane wall thickness is 0.6 mm.
[0051] The weight ratio of pre-modified activated carbon, anhydrous ethanol, polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate is 7:100:12:1.4:0.08.
[0052] The volume ratio of the dry silicone rubber / polysulfone hollow fiber composite membrane to the primary treatment liquid is 1:3.
[0053] 3) Secondary processing
[0054] The pre-modified activated carbon was put into deionized water, stirred for 10 minutes, and then zinc nitrate hexahydrate and 2-methylimidazole were added, and stirred for 20 minutes to obtain a secondary treatment liquid; then the primary treatment composite membrane was completely immersed in the secondary treatment liquid. After immersion for 30 minutes, the immersed primary treatment composite membrane was taken out and transferred to a constant temperature box. After standing at 50°C for 2 hours, it was dried at 90°C for 4 hours to obtain a modified hollow fiber composite membrane.
[0055] Wherein, the weight ratio of pre-modified activated carbon, deionized water, zinc nitrate hexahydrate and 2-methylimidazole is 4:300:0.6:8.3.
[0056] The volume ratio of the primary treatment composite membrane to the secondary treatment liquid is 1:2.5.
[0057] 2. Concentration
[0058] Industrial-grade hydrogen peroxide with a mass concentration of 28% is introduced into a falling film evaporator, concentrated to a mass concentration of 50% by falling film evaporation, and concentrated hydrogen peroxide is obtained and introduced into a temporary storage tank to be cooled to room temperature for standby use.
[0059] 3. Primary membrane separation
[0060] After the modified hollow fiber composite membrane is assembled into the hollow fiber membrane module, it is respectively loaded into the primary membrane separation device and the secondary membrane separation device, and the concentrated hydrogen peroxide in the temporary storage tank is continuously introduced into the primary membrane separation device, and the inlet flow rate of the concentrated hydrogen peroxide is controlled to be 380kg / h, and the membrane separation pressure is 0.23MPa. After continuous primary membrane separation, the primary membrane separation liquid is obtained and continuously introduced into the secondary membrane separation device.
[0061] Among them, the effective membrane area of the first-stage membrane separation device is 18m 2 .
[0062] 4. Secondary membrane separation
[0063] The secondary membrane separation device continuously receives the primary membrane separation liquid from the primary membrane separation device, controls the membrane separation pressure to be 0.27MPa, and after continuously performing the secondary membrane separation, obtains the purified hydrogen peroxide product, which is continuously introduced into the product tank for storage.
[0064] Among them, the effective membrane area of the secondary membrane separation device is 23m 2 .
[0065] At the same time, in order to maintain the ideal membrane separation treatment effect and treatment stability under the membrane separation conditions of continuous, large flow and high operating pressure, the modified hollow fiber composite membrane in the primary membrane separation device and the secondary membrane separation device is backwashed once every 24 hours, and each backwashing time is 60 seconds.
[0066] Example 2
[0067] The present embodiment provides a method for purifying hydrogen peroxide, which purifies industrial-grade hydrogen peroxide prepared by an anthraquinone method; the mass concentration of the industrial-grade hydrogen peroxide is 28%, the organic carbon content TOC is 557 ppm, the chloride content is 303 ppb, the nitrate content is 50 ppb, the sulfate content is 78 ppb, the phosphate content is 42 ppb, the silicon content is 51 ppb, the calcium content is 10 ppt, the potassium content is 77 ppt, the sodium content is 168 ppt, and the iron content is 16 ppt.
[0068] Specifically, the method for purifying the hydrogen peroxide is as follows:
[0069] 1. Preparation of modified hollow fiber composite membrane
[0070] 1) Preparation of pre-modified activated carbon
[0071] The nano-activated carbon was put into a reactor filled with toluene, and after stirring for 25 minutes, acrylic ester monomers, cross-linking monomers and silane modifiers were continuously added, and then the air in the reactor was completely replaced by nitrogen. Under the protection of nitrogen atmosphere, the temperature was raised to 52°C with stirring, and after stirring and keeping warm for 35 minutes, the temperature was raised to 82°C with stirring and keeping warm; the initiator was stirred and added, and the stirring and keeping warm were continued for 3 hours. After cooling to room temperature, the solid matter was separated by filtration to obtain the solid matter; the solid matter was washed 3 times with 4.5 times the weight of toluene, and then dried to obtain pre-modified activated carbon.
[0072] Among them, the average particle size of nano activated carbon is 90nm.
[0073] The acrylic acid ester monomers are n-butyl methacrylate and methyl acrylate; the weight ratio of n-butyl methacrylate to methyl acrylate is 3.1:1.
[0074] The cross-linking monomer is N,N-dimethyl methacrylamide.
[0075] The silane modifier is methacryloxymethyltriethoxysilane.
[0076] The initiator is azobisisobutyronitrile.
[0077] The weight ratio of nano activated carbon, toluene, acrylate monomer, cross-linking monomer, silane modifier and initiator is 15.5:83:65:7.7:3.1:2.2.
[0078] 2) One-time processing
[0079] The pre-modified activated carbon was put into anhydrous ethanol, stirred for 15 minutes, and then polymethyloctylsiloxane, silane coupling agent KH-550 and dibutyltin dilaurate were added, and stirred for 25 minutes to obtain a primary treatment liquid; then the dried silicone rubber / polysulfone hollow fiber composite membrane was completely immersed in the primary treatment liquid, and the immersion pressure was controlled to be 0.14MPa. After immersion for 40 seconds, the impregnated silicone rubber / polysulfone hollow fiber composite membrane was taken out and transferred to a constant temperature box. After drying at 88°C for 4.5 hours, the temperature was raised to 138°C and heat-treated for 25 minutes to obtain a primary treatment composite membrane.
[0080] The pore size of the silicone rubber / polysulfone hollow fiber composite membrane is 0.25 μm, the inner diameter of the membrane is 0.8 mm, and the membrane wall thickness is 0.6 mm.
[0081] The weight ratio of pre-modified activated carbon, anhydrous ethanol, polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate is 7.1:102:12.5:1.45:0.09.
[0082] The volume ratio of the dry silicone rubber / polysulfone hollow fiber composite membrane to the primary treatment liquid is 1:3.3.
[0083] 3) Secondary processing
[0084] The pre-modified activated carbon was put into deionized water, stirred for 15 minutes, and then zinc nitrate hexahydrate and 2-methylimidazole were added, and stirred for 25 minutes to obtain a secondary treatment liquid; then the primary treatment composite membrane was completely immersed in the secondary treatment liquid. After immersion for 35 minutes, the immersed primary treatment composite membrane was taken out and transferred to a constant temperature box. After standing at 52°C for 2.5 hours, it was dried at 93°C for 4.5 hours to obtain a modified hollow fiber composite membrane.
[0085] Among them, the weight ratio of pre-modified activated carbon, deionized water, zinc nitrate hexahydrate and 2-methylimidazole is 4.3:302:0.61:8.35.
[0086] The volume ratio of the primary treatment composite membrane to the secondary treatment liquid is 1:2.7.
[0087] 2. Concentration
[0088] Industrial-grade hydrogen peroxide with a mass concentration of 28% is introduced into a falling film evaporator, concentrated to a mass concentration of 52% by falling film evaporation, and concentrated hydrogen peroxide is obtained and introduced into a temporary storage tank to be cooled to room temperature for standby use.
[0089] 3. Primary membrane separation
[0090] After the modified hollow fiber composite membrane is assembled into the hollow fiber membrane module, it is respectively loaded into the primary membrane separation device and the secondary membrane separation device, and the concentrated hydrogen peroxide in the temporary storage tank is continuously introduced into the primary membrane separation device, and the inlet flow rate of the concentrated hydrogen peroxide is controlled to be 390kg / h, and the membrane separation pressure is 0.24MPa. After continuous primary membrane separation, the primary membrane separation liquid is obtained and continuously introduced into the secondary membrane separation device.
[0091] Among them, the effective membrane area of the first-stage membrane separation device is 19.1m 2 .
[0092] 4. Secondary membrane separation
[0093] The secondary membrane separation device continuously receives the primary membrane separation liquid from the primary membrane separation device, controls the membrane separation pressure to be 0.28MPa, and after continuously performing the secondary membrane separation, obtains the purified hydrogen peroxide product, which is continuously introduced into the product tank for storage.
[0094] Among them, the effective membrane area of the secondary membrane separation device is 24.2m 2 .
[0095] At the same time, in order to maintain the ideal membrane separation treatment effect and treatment stability under the membrane separation conditions of continuous, large flow and high operating pressure, the modified hollow fiber composite membrane in the primary membrane separation device and the secondary membrane separation device is backwashed once every 24 hours, and each backwashing time is 60 seconds.
[0096] Example 3
[0097] The present embodiment provides a method for purifying hydrogen peroxide, which purifies industrial-grade hydrogen peroxide prepared by an anthraquinone method; the mass concentration of the industrial-grade hydrogen peroxide is 28%, the organic carbon content TOC is 557 ppm, the chloride content is 303 ppb, the nitrate content is 50 ppb, the sulfate content is 78 ppb, the phosphate content is 42 ppb, the silicon content is 51 ppb, the calcium content is 10 ppt, the potassium content is 77 ppt, the sodium content is 168 ppt, and the iron content is 16 ppt.
[0098] Specifically, the method for purifying the hydrogen peroxide is as follows:
[0099] 1. Preparation of modified hollow fiber composite membrane
[0100] 1) Preparation of pre-modified activated carbon
[0101] The nano-activated carbon was put into a reactor filled with toluene, and after stirring for 30 minutes, acrylic ester monomers, cross-linking monomers and silane modifiers were continuously added, and then the air in the reactor was completely replaced by nitrogen. Under the protection of nitrogen atmosphere, the temperature was raised to 55°C with stirring, and after stirring and keeping warm for 40 minutes, the temperature was raised to 85°C with stirring and keeping warm; the initiator was stirred and added, and the stirring and keeping warm for 3.5 hours was continued. After cooling to room temperature, the solid matter was separated by filtration to obtain the solid matter; the solid matter was washed 3 times with 5 times the weight of toluene, and then dried to obtain the pre-modified activated carbon.
[0102] Among them, the average particle size of nano activated carbon is 90nm.
[0103] The acrylic acid ester monomers are n-butyl methacrylate and methyl acrylate; the weight ratio of n-butyl methacrylate to methyl acrylate is 3.2:1.
[0104] The cross-linking monomer is N,N-dimethyl methacrylamide.
[0105] The silane modifier is methacryloxymethyltriethoxysilane.
[0106] The initiator is azobisisobutyronitrile.
[0107] The weight ratio of nano activated carbon, toluene, acrylate monomer, cross-linking monomer, silane modifier and initiator is 16:85:66:8:3.3:2.5.
[0108] 2) One-time processing
[0109] The pre-modified activated carbon was put into anhydrous ethanol, stirred for 20 minutes, and then polymethyloctylsiloxane, silane coupling agent KH-550 and dibutyltin dilaurate were added, and stirred for 30 minutes to obtain a primary treatment liquid; then the dried silicone rubber / polysulfone hollow fiber composite membrane was completely immersed in the primary treatment liquid, and the immersion pressure was controlled to be 0.15MPa. After immersion for 50 seconds, the impregnated silicone rubber / polysulfone hollow fiber composite membrane was taken out and transferred to a constant temperature box. After drying at 90°C for 5 hours, the temperature was raised to 140°C and heat-treated for 30 minutes to obtain a primary treatment composite membrane.
[0110] The pore size of the silicone rubber / polysulfone hollow fiber composite membrane is 0.25 μm, the inner diameter of the membrane is 0.8 mm, and the membrane wall thickness is 0.6 mm.
[0111] The weight ratio of pre-modified activated carbon, anhydrous ethanol, polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate is 7.2:105:13:1.5:0.1.
[0112] The volume ratio of the dry silicone rubber / polysulfone hollow fiber composite membrane to the primary treatment liquid is 1:3.5.
[0113] 3) Secondary processing
[0114] The pre-modified activated carbon was put into deionized water, stirred for 20 minutes, and then zinc nitrate hexahydrate and 2-methylimidazole were added, and stirred for 30 minutes to obtain a secondary treatment liquid; then the primary treatment composite membrane was completely immersed in the secondary treatment liquid. After immersion for 40 minutes, the immersed primary treatment composite membrane was taken out and transferred to a constant temperature box. After standing at 55°C for 3 hours, it was dried at 95°C for 5 hours to obtain a modified hollow fiber composite membrane.
[0115] Among them, the weight ratio of pre-modified activated carbon, deionized water, zinc nitrate hexahydrate and 2-methylimidazole is 4.5:305:0.62:8.4.
[0116] The volume ratio of the primary treatment composite membrane to the secondary treatment liquid is 1:3.
[0117] 2. Concentration
[0118] Industrial-grade hydrogen peroxide with a mass concentration of 28% is introduced into a falling film evaporator, concentrated to a mass concentration of 55% by falling film evaporation, and concentrated hydrogen peroxide is obtained and introduced into a temporary storage tank to be cooled to room temperature for standby use.
[0119] 3. Primary membrane separation
[0120] After the modified hollow fiber composite membrane is assembled into the hollow fiber membrane module, it is respectively loaded into the primary membrane separation device and the secondary membrane separation device, and the concentrated hydrogen peroxide in the temporary storage tank is continuously introduced into the primary membrane separation device, and the inlet flow rate of the concentrated hydrogen peroxide is controlled to be 400kg / h, and the membrane separation pressure is 0.25MPa. After continuous primary membrane separation, the primary membrane separation liquid is obtained and continuously introduced into the secondary membrane separation device.
[0121] Among them, the effective membrane area of the first-stage membrane separation device is 20m 2 .
[0122] 4. Secondary membrane separation
[0123] The secondary membrane separation device continuously receives the primary membrane separation liquid from the primary membrane separation device, controls the membrane separation pressure to be 0.3MPa, and after continuously performing the secondary membrane separation, obtains the purified hydrogen peroxide product, which is continuously introduced into the product tank for storage.
[0124] Among them, the effective membrane area of the secondary membrane separation device is 25m 2 .
[0125] At the same time, in order to maintain the ideal membrane separation treatment effect and treatment stability under the membrane separation conditions of continuous, large flow and high operating pressure, the modified hollow fiber composite membrane in the primary membrane separation device and the secondary membrane separation device is backwashed once every 24 hours, and each backwashing time is 60 seconds.
[0126] Comparative Example 1
[0127] The technical solution of Example 2 is adopted, but the differences are: 1) the step of preparing pre-modified activated carbon is omitted, and untreated nano-activated carbon is used instead of pre-modified activated carbon for subsequent steps; 2) the secondary treatment step is omitted, and the once-treated composite membrane is used in subsequent primary membrane separation and secondary membrane separation.
[0128] Comparative Example 2
[0129] The technical scheme of Example 2 is adopted, but the differences are as follows: 1) in the step of preparing pre-modified activated carbon, the addition of cross-linking monomer and silane modifier is omitted; 2) the primary treatment step is omitted, and the dried silicone rubber / polysulfone hollow fiber composite membrane is directly treated after the pre-modified activated carbon is prepared with zinc nitrate hexahydrate and 2-methylimidazole into a secondary treatment liquid.
[0130] The industrial-grade hydrogen peroxide obtained by the anthraquinone method was purified by the hydrogen peroxide purification method of Examples 1-3 and Comparative Examples 1-2. At 8 hours after the first and second membrane separations were performed continuously, the purified hydrogen peroxide product obtained by the second membrane separation was sampled and tested. The organic carbon content, chloride, nitrate, sulfate, phosphate, silicon content, calcium content, potassium content, sodium content, iron content, and evaporation residue content in the hydrogen peroxide product were tested. The specific results are shown in the following table:
[0131]
[0132] Furthermore, the water contact angle of the modified hollow fiber composite membrane prepared in the hydrogen peroxide purification method of Example 1-3 and Comparative Example 1-2 was tested; at the same time, in the hydrogen peroxide purification method of Example 1-3 and Comparative Example 1-2, after each modified hollow fiber composite membrane in the primary membrane separation device was continuously operated for 90 days, the water contact angle of each modified hollow fiber composite membrane was tested. The specific results are shown in the following table:
[0133]
[0134] Further, the hydrogen peroxide purification method of Examples 1-3 and Comparative Examples 1-2 was used to purify the industrial-grade hydrogen peroxide obtained by the anthraquinone method. On the 90th day of continuous primary membrane separation and secondary membrane separation, the purified hydrogen peroxide product obtained by the secondary membrane separation was sampled and tested, and the organic carbon content, chloride, nitrate, sulfate, phosphate, silicon content, calcium content, potassium content, sodium content, iron content, and evaporation residue content in the hydrogen peroxide product were tested. At the same time, in order to maintain the best membrane separation performance, the backwashing interval required for the modified hollow fiber composite membrane in the primary membrane separation device and the secondary membrane separation device was counted.
[0135] The specific results are shown in the following table:
[0136]
[0137] It can be seen that in the preparation of the modified hollow fiber composite membrane, in the step of preparing the pre-modified activated carbon, the nano-activated carbon is treated with a combination of acrylate monomers, cross-linking monomers and silane modifiers, which can introduce cross-linkable groups (acrylate groups, silane groups, etc.) on the surface of the nano-activated carbon, effectively improve the subsequent composite performance of the pre-modified activated carbon and silicone rubber, and at the same time improve the hydrophobicity of the nano-activated carbon; then in a treatment step, the pre-modified activated carbon is combined with polymethyloctylsiloxane and silane coupling agent KH-550 through the cross-linkable groups on its surface, and through the combination with silicone rubber The cross-linked compound of monomers can be effectively compounded to the outer surface of silicone rubber / polysulfone hollow fiber composite membrane to form a cross-linked porous composite structure, and the hydrophobicity of the primary treatment composite membrane can be further improved by the silane coupling agent KH-550, so as to avoid the attachment and aggregation of water molecules on the surface of the membrane material and improve the stability of the continuous membrane separation treatment; by compounding pre-modified activated carbon, polymethyloctylsiloxane and silicone rubber / polysulfone hollow fiber composite membrane, it is possible to improve the stability and oxidation resistance of the membrane material while improving its mechanical properties, and improve its resistance to adverse factors during application. , extending the service life; then in the secondary treatment step, the pre-modified activated carbon is used in combination with the in-situ generated metal organic framework material, through chemical bonding and interface bonding, to further improve the stability, oxidation resistance and mechanical properties of the membrane material, extend the effective service life of the membrane material, improve the adaptability and separation stability of the membrane material to continuous, large flow, and high operating pressure, and at the same time improve the targeted separation performance of the membrane material for impurities (especially metal impurities) in hydrogen peroxide; then the industrial-grade hydrogen peroxide is concentrated, separated by a primary membrane, and separated by a secondary membrane to obtain a purified hydrogen peroxide product; the aforementioned technical means cooperate and work synergistically with each other, and can effectively avoid the adverse effects of the strong oxidizing property of high-concentration hydrogen peroxide on the membrane material under the membrane separation conditions of continuous, large flow, and high operating pressure, while maintaining the good service life and mechanical properties of the membrane material, further avoid the adverse effects of metal impurities in concentrated hydrogen peroxide on the membrane material, can synchronously separate organic impurities and metal impurities in concentrated hydrogen peroxide, and realize continuous and effective purification of hydrogen peroxide; and in the continuous membrane separation process, effectively avoid the attachment and aggregation of water molecules on the surface of the membrane material, and improve the stability of continuous processing.
[0138] Unless otherwise specified, all percentages used in the present invention are by mass.
[0139] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for purifying hydrogen peroxide, characterized in that: The method comprises the following steps: preparing a modified hollow fiber composite membrane, concentrating, primary membrane separation, and secondary membrane separation; The preparation of the modified hollow fiber composite membrane comprises the following steps: preparation of pre-modified activated carbon, primary treatment, and secondary treatment; The method for preparing pre-modified activated carbon comprises: adding nano activated carbon, acrylic ester monomer, cross-linking monomer and silane modifier into toluene, mixing evenly under nitrogen atmosphere, heating to 80-85° C., keeping the temperature and adding initiator, keeping the temperature for reaction, cooling, separating and obtaining solids, washing and drying the solids to obtain pre-modified activated carbon; In the preparation of the pre-modified activated carbon, the acrylate monomers are n-butyl methacrylate and methyl acrylate; the crosslinking monomer is N,N-dimethyl methacrylamide; and the silane modifier is methacryloxymethyl triethoxysilane; The method for the one-time treatment is as follows: pre-modified activated carbon, polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate are added into anhydrous ethanol to obtain a one-time treatment liquid; a dried silicone rubber / polysulfone hollow fiber composite membrane is immersed in the one-time treatment liquid, dried after immersion, and then subjected to heat treatment at 135-140° C. to obtain a one-time treatment composite membrane; In the one-time treatment, the pore size of the silicone rubber / polysulfone hollow fiber composite membrane is 0.2-0.3 μm, the inner diameter of the membrane is 0.7-0.8 mm, and the membrane wall thickness is 0.5-0.6 mm; The secondary treatment method comprises: adding pre-modified activated carbon, zinc nitrate hexahydrate, and 2-methylimidazole into deionized water to obtain a secondary treatment solution; immersing the primary treatment composite membrane into the secondary treatment solution, standing at a temperature of 50-55° C. after immersion, and drying to obtain a modified hollow fiber composite membrane; The concentration method is to concentrate the hydrogen peroxide to a mass concentration of 50-55% to obtain concentrated hydrogen peroxide; The primary membrane separation method is to continuously perform primary membrane separation on concentrated hydrogen peroxide using a modified hollow fiber composite membrane to continuously obtain a primary membrane separation liquid; In the primary membrane separation, the flow rate of concentrated hydrogen peroxide is 380-400 kg / h, and the primary membrane separation pressure is 0.23-0.25 MPa; The secondary membrane separation method is to use a modified hollow fiber composite membrane to continuously perform secondary membrane separation on the primary membrane separation liquid to continuously obtain purified hydrogen peroxide; In the secondary membrane separation, the secondary membrane separation pressure is 0.27-0.3 MPa.
2. The method for purifying hydrogen peroxide according to claim 1, wherein In the preparation of the pre-modified activated carbon, the weight ratio of n-butyl methacrylate to methyl acrylate is 3-3.2:
1.
3. The method for purifying hydrogen peroxide according to claim 1, wherein In the preparation of the pre-modified activated carbon, the weight ratio of the nano-activated carbon, toluene, acrylic ester monomer, cross-linking monomer, silane modifier and initiator is 15-16:80-85:63-66:7-8:3-3.3:2-2.
5.
4. The method for purifying hydrogen peroxide according to claim 1, wherein In the preparation of the pre-modified activated carbon, the heat preservation reaction time is 2.5-3.5h; The initiator is azobisisobutyronitrile; The average particle size of nano activated carbon is 90-100nm.
5. The method for purifying hydrogen peroxide according to claim 1, characterized in that: In the one-time treatment, the immersion pressure is 0.12-0.15 MPa, and the immersion time is 30-50 s; The heat treatment time at 135-140℃ is 20-30min.
6. The method for purifying hydrogen peroxide according to claim 1, characterized in that: In the one-time treatment, the weight ratio of pre-modified activated carbon, anhydrous ethanol, polymethyloctylsiloxane, silane coupling agent KH-550, and dibutyltin dilaurate is 7-7.2:100-105:12-13:1.4-1.5:0.08-0.1; The volume ratio of the dry silicone rubber / polysulfone hollow fiber composite membrane to the primary treatment liquid is 1:3-3.
5.
7. The method for purifying hydrogen peroxide according to claim 1, wherein In the secondary treatment, the standing time at 50-55°C is 2-3h; The weight ratio of pre-modified activated carbon, deionized water, zinc nitrate hexahydrate, and 2-methylimidazole is 4-4.5:300-305:0.6-0.62:8.3-8.4; The volume ratio of the primary treatment composite membrane to the secondary treatment liquid is 1:2.5-3.
Citation Information
Patent Citations
Production method and production device of electronic-grade hydrogen peroxide
CN115557470A
Preparation method of silicone rubber composite hollow fibrous membrane
CN104084052A
Method for separation and purification of hydrogen peroxide
CN109205571A
Preparation method of ultrathin silicone rubber / MOF hollow fiber composite membrane
CN116116241A